2017
DOI: 10.1002/cam4.1084
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐TCONS_00026907 is involved in the progression and prognosis of cervical cancer through inhibiting miR‐143‐5p

Abstract: Our previous long noncoding RNA (lncRNA) microarray revealed that lncRNA‐TCONS_00026907 is aberrantly expressed between cervical cancer tissues and adjacent tissues. This study aims to explore the potential role of TCONS_00026907 in the development of cervical cancer. The expression levels of TCONS_00026907 in cervical cancer tissues and adjacent tissues from 83 patients of cervical cancer were detected by quantitative real‐time polymerase chain reaction and the survival rate was analyzed. In vitro, HeLa and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 45 publications
(46 reference statements)
4
46
0
Order By: Relevance
“…Cervical cancer is one of the most common malignant tumors, and its incidence is only preceded by breast cancer [ 1 2 ]. In recent years, more attention is paid to study the role of lncRNA in cervical cancer [ 39 40 ]. In our previous study, lncRNA XLOC_006390 was found to exhibit abnormal expression in cervical cancer cells and influence cervical cancer cell proliferation and migration by regulating downstream SET8 proteins [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is one of the most common malignant tumors, and its incidence is only preceded by breast cancer [ 1 2 ]. In recent years, more attention is paid to study the role of lncRNA in cervical cancer [ 39 40 ]. In our previous study, lncRNA XLOC_006390 was found to exhibit abnormal expression in cervical cancer cells and influence cervical cancer cell proliferation and migration by regulating downstream SET8 proteins [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA CASC2 can suppress epithelial‐mesenchymal transition of hepatocellular carcinoma cells via targeting miR‐367 (Wang, Liu et al, ). LncRNA‐TCONS_00026907 is involved in cervical cancer progression through inhibiting miR‐143‐5p (Jin et al, ). LncRNA MALAT1 can promote metastasis and proliferation by acting as a ceRNA of miR‐144‐3p in osteosarcoma cells (Wang, Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the interactions between lncRNAs and miRNAs in human carcinomas are attracting more and more attention these days. LncRNA‐TCONS_00026907 is found to regulate the progression cervical cancer by targeting miR‐143‐5p (Jin et al, ). By inhibiting miR‐874, lncRNA‐XLOC_008466 can promote human non‐small cell lung cancer development (Yang, Ruan, Hu, Cao, & Song, ).…”
Section: Discussionmentioning
confidence: 99%